Assessment of the Medical Reliability of Videos on Social Media: Detailed Analysis of the Quality and Usability of Four Social Media Platforms (Facebook, Instagram, Twitter, and YouTube) - Gurler, Deniz; Buyukceran, Ismail (MDPI, 2022)
Introduction: In recent years, the internet and social media have become the primary source for patients to research their medical conditions. Given the billions of links that result from research, it has become increasingly important how medically high quality the priorities of the search algorithms are. This study aims to examine the medical quality of videos on social media. Material and Method: A new Gmail account was never used, and Facebook, Instagram, Twitter, and YouTube accounts were opened. The word "knee replacement" was searched via social media. The video duration, daily views, total views, number of likes, source, and shared content were recorded. The parameters were statistically evaluated using the scales JAMA, GQS, DISCERN, and VPI to measure the quality of the medical posts. Results: Correlations were found between JAMA, GQS, and DISCERN. No correlation between the VPI scales with other scales was found. It was found that the promotional content in videos other than Instagram was very high (56-70%). Academics and healthcare workers produced greater quality content than other groups. There is a clear dominance of healthcare practitioners on Instagram. The most shared content was informative, depending on the content. The most frequent users were alternative health practitioners. While YouTube had the highest JAMA, GQC, and DISCERN (2.98, 3.18, 37.5) scores, the lowest VPI (0.761) score was found. Discussion and Conclusions: It has been shown that Instagram and Twitter are not the right places to share videos with medical content. However, everyone should remember that Instagram is the best place to share short but popular videos. YouTube and Facebook are available resources to share videos of better medical quality with a higher score than others. We can say that the most reliable medical sources are Facebook and YouTube videos of physicians and medical staff.
Keywords: Social Media; YouTube; Instagram; Twitter; Facebook; Video; Knee Replacement